The Influence of Formal and Informal Education on Students’ Sustainable Development Skills, a Study in Iran - Pouratashi Mahtab (Sciendo, 2021)
This study aimed to understand the influence of formal and informal education on students’ sustainable development skills. A sample of 567 students studying Humanities, Agriculture, or Engineering at public universities of Iran participated in this study. A survey was used to investigate students’ skills for sustainable development according to different forms of education. Students’ sustainable development skills were assessed including: empathy, participatory skill, systemsthinking, creative thinking, and anticipatory thinking. The results indicated that students had a good level of skills for sustainable development. Differences and similarities were found on students’ skills by different forms of education and learning. The findings confirmed that education is useful to improve individuals’ skills for sustainable development and confirmed the key role of education for sustainable development in addressing sustainable future.